Volume 2A: Turbomachinery 2014
DOI: 10.1115/gt2014-25073
|View full text |Cite
|
Sign up to set email alerts
|

Ejector Tip Injection for Active Compressor Stabilization

Abstract: In propulsion industry there is an ongoing need to significantly reduce SFC of jet engines resulting in cost reduction and lower emissions. Since the design of most of the engine components is at the limit of today’s technology level further gain of improvement on short term is to be achieved by implementation of new system concepts. Especially the stall safety margin in compression system design holds high potential for the optimization of the overall engine system. Once a reliable and effective stall control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the conventional tip injection designs, the pressurized HPC or shop air is injected directly into the tip region of the compressor. The studies by Kefalakis and Papailiou (2006), Bindl et al (2009a) and Stößel et al (2014) showed that a higher injection mass flow rate is advantageous for the tip injection. Therefore, ejector tip injection utilizes the pressurized air as primary mass flow, which is is injected into an ejector geometry inside the EIS.…”
Section: Concept and Design Fundamentalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the conventional tip injection designs, the pressurized HPC or shop air is injected directly into the tip region of the compressor. The studies by Kefalakis and Papailiou (2006), Bindl et al (2009a) and Stößel et al (2014) showed that a higher injection mass flow rate is advantageous for the tip injection. Therefore, ejector tip injection utilizes the pressurized air as primary mass flow, which is is injected into an ejector geometry inside the EIS.…”
Section: Concept and Design Fundamentalsmentioning
confidence: 99%
“…This system only activates the air injection, if a stall event is directly imminent, which helps to increase the overall efficiency of the jet engine. In order to increase the efficiency of the tip injection, Stößel et al (2014) extended the existing injection system with an ejector. With this modification, a surge margin increase between 5 % and 60 % (depending on injection mass flow and operating point) was observed.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Niehuis et al (2012)). Stößel et al (2014) have proven experimentally that deploying the ejector effect in the previously described manner can significantly improve impact and efficiency of the entire air injection concept. Based on these findings, a further advanced Ejector Injection System (EIS) has been developed by Kern et al (2017) and is currently under investigation.…”
Section: Introductionmentioning
confidence: 96%
“…In parallel Active control technics, and more precisely discrete tip injection, have shown their effectiveness on the improvement of the compressor stability by moving away the surge line (Suder et al 2001;Nie et al 2002;Kefalakis and Papailiou 2007;Li et al 2014). Some successful applications have also been demonstrated on real aircraft engines (Stößel et al 2013(Stößel et al , 2014. Understanding their effects is thus of first interest but surprisingly, few works have investigated the mechanisms involved when active flow control is applied and how it affects the flow patterns in the tip gap while extensive work in this domain has been done with casing treatments (Takata and Tsukuda 1977;Smith and Cumpsty 1983;Fujita and Takata 1984;Cumpsty 1989).…”
Section: Introductionmentioning
confidence: 99%